Sterilization of health care products. Liquid chemical sterilizing agents for single-use medical devices utilizing animal tissues and their derivatives. Requirements for characterization, development, validation and routine control of a sterilization process for medical devices. (5th July 2021) - British Standards Institution,
No abstract available